The role of the exchange and correlation term in the lattice dynamics of alkali metals. - Blanchard, Robert. (University of Ottawa (Canada), 1969)
The contents of the present thesis can be described as follows. In chapter II the work of Hone (H60) is extended and the results are combined with those of Bailyn (B60). A unified approach is given to the derivation of the "proton-electron" dielectric function, with simplifications achieved by the removal of certain unnecessary transformations. A discussion of electron-electron screening shows why many of the results derived from Bailyn's and Hone's work are similar. In chapter III new derivations are given for the exchange and correlation terms obtained by several authors, namely Toya (T58), Hubbard (H57), Geldart-Vosko (G65), Kleinman (K67), and Takahashi (T68). We then show that electron-electron screening can be described in a more accurate way, and using a factorization procedure (introduced in chapter II), new expressions for the exhange and correlation term are obtained. In chapter IV we present the lattice dynamics of sodium, potassium and rubidium. Cochran's (C63) method of obtaining empirical effective potentials from the dispersion curves is discussed to obtain some insight into the problem. Then the method of Cowley et al (C66) is applied; a choice of the dielectric function is made, the pseudopotentials are determined and compared to those obtained by least squares fitting of different models. Finally, the dispersion curves are calculated and the interatomic potentials are also obtained.
Keywords: Physics, Atomic.